Effect of think-pair-share strategy on senior secondary school students’ performance in reading comprehension in Gombe State, Nigeria - Hussaini, Hadiza; Mohammed, Suwaiba (Kashere Journal of Education, 2023)
This study focused on examining the effect of think-pair-share strategy (TPS) of teaching reading comprehension on the performance of senior secondary school students in Gombe state, Nigeria. The target population comprised all senior secondary school students in 134 public secondary schools in Gombe. Simple random sampling technique was used to select two intact classes in two secondary schools which gave a sample of 91 students were used for the study. Quasi experimental research design with pre-test post-test experimental and control group were used with 47 students in the experimental group and 44 students in the control group. Data was collected using reading comprehension test. The reading comprehension test had a reliability index of 0.81 using test rest method while analysis was run using mean, standard deviation for the research question and independent sample t-test for research hypothesis. Results showed a mean difference of 1.76 and 0.21 for experimental and control groups respectively indicating that the former group achieved a higher score when compared with their counterparts from the control group in the reading comprehension test. Hence, it was concluded that the TPS strategy used in the reading comprehension class has significantly influenced students’ performance in reading comprehension. Recommendations were that English language teachers should use the think-pair-share strategy to improve active participation of students in reading comprehension class and beyond.